Interactions of Nitrosylhemolgoin and Carboxyhemoglobin with Erythrocyte - Chou, Katherine J. (2007)
Nitrosylhemoglobin (HbFe(II)NO) has been detected in vivo, and its role in NO transport and preservation has been discussed. To gain insight into the potential role of HbFe(II)NO, we performed in vitro experiments to determine the effect of oxygenated red blood cells (RBCs) on the dissociation of cell-free HbFe(II)NO, using carboxyhemoglobin (HbFe(II)CO) as a comparison. Results show that the apparent half-life of the cell-free HbFe(II)CO was reduced significantly in the presence of RBCs at 1 % hematocrit. In contrast, RBC did not change the apparent half-life of extracellular HbFe(II)NO, but caused a shift in the HbFe(II)NO dissociation product from methemoglobin (metHbFe(III)) to oxyhemoglobin (HbFe(II)O(2)). Extracellular hemoglobin was able to extract CO from HbFe(II)CO-containing RBC, but not NO from HbFe(II)NO-containing RBC. Although these results appear to suggest some unusual interactions between HbFe(II)NO and RBC, the data are explainable by simple HbFe(II)NO dissociation and hemoglobin oxidation with known rate constants. A kinetic model consisting of these reactions shows that i) deoxyhemoglobin is an intermediate in the reaction of HbFe(II)NO oxidation to metHbFe(III), ii) the rate-limiting step of HbFe(II)NO decay is the dissociation of NO from HbFe(II)NO, iii) the magnitude of NO diffusion rate constant into RBC is estimated to be ∼10(4) M(-1)s(-1), consistent with previous results determined from a competition assay, and iv) no additional chemical reactions are required to explain these data.